The Effect of Experimental Recuperative and Appetitive Post-lunch Nap Opportunities, With or Without Caffeine, on Mood and Reaction Time in Highly Trained Athletes - Romdhani, Mohamed; Souissi, Nizar; Dergaa, Ismael; Moussa-Chamari, Imen; Abene, Olfa; Chtourou, Hamdi; Sahnoun, Zouheir; Driss, Tarak; Chamari, Karim; Hammouda, Omar (Frontiers in Psychology, 2021)
Purpose: to investigate the effects of 20 min nap opportunity (N20), 5mg·kg-1 of caffeine (CAF), and their combination (CAF+N20) on sleepiness, mood and reaction-time after partial sleep deprivation (PSD; 04h30 of time in bed; study 1) or after normal sleep night (NSN; 08h30 of time in bed; study 2). Methods: twenty-three highly trained athletes (study 1; 9 and study 2; 14) performed four test sessions (PLA, CAF, N20 and CAF+N20) in double-blind, counterbalanced and randomized order. Simple (SRT) and two-choice (2CRT) reaction time, subjective sleepiness (ESS) and mood state (POMS) were assessed twice, pre- and post-intervention. Results: SRT was lower (i.e., better performance) during CAF condition after PSD (pre: 336±15 ms vs. post: 312±9 ms; p<0.001; d=2.07; Δ%=7.26) and NSN (pre: 350±39 ms vs. post: 323±32 ms; p<0.001; d=0.72; Δ%=7.71) compared to pre-intervention. N20 decreased 2CRT after PSD (pre: 411±13 ms vs. post: 366±20 ms; p<0.001; d=2.89; Δ%=10.81) and NSN (pre: 418±29 ms vs. post: 375±40 ms; p<0.001; d =1.23; Δ%=10.23). Similarly, 2CRT was shorter during CAF+N20 sessions after PSD (pre: 406±26 ms vs. post: 357±17 ms; p<0.001; d=2.17; Δ%=12.02) and after NSN (pre: 386±33 ms vs. post: 352±30 ms; p<0.001; d=1.09; Δ%=8.68). After PSD, POMS score decreased after CAF (p<0.001; d=2.38; Δ%=66.97) and CAF+N20 (p<0.001; d=1.68; Δ%=46.68). However, after NSN, only N20 reduced POMS (p<0.001; d=1.05; Δ%=78.65) and ESS (p<0.01; d=0.71; Δ%=19.11). Conclusion: After PSD, all interventions reduced sleepiness and only CAF enhanced mood with or without napping. However, only N20 enhanced mood and reduced sleepiness after NSN. Caffeine ingestion enhanced SRT performance regardless of sleep deprivation. N20, with or without caffeine ingestion, enhanced 2CRT independently of sleep deprivation. This suggests a different mode of action of napping and caffeine on sleepiness, mood and reaction time.